A Taxonomy of the Real: Seoul. Issue 3 (1st September 2016) - Ferretto, Peter W.
Abstract: This paper explores the relationship between the actual (what happens) and the real (what is meaningful) about the contemporary city. The argument focuses on Seoul, the capital of South Korea, as an example of a modern metropolis designed by agents of capitalism rather than architects or planners. The resulting dynamic collage can be best defined as an unsolicited urban condition, steering away from typical models seeking to regulate and impose order, and towards an adaptive urban fabric in constant transition. At the heart of Seoul's DNA is the absence of grids. Unlike its neighbouring capitals – Beijing and Tokyo – Seoul is a capital whose urban fabric developed in direct symbiosis with its topography, resulting in urban fragments in a state of flux becoming the very marrow of urban life where apparently incongruous elements collide to generate new reciprocities of precarious coexistence.